The relationship between deltamethrin-induced behavioral changes and acetylcholinesterase activity in zebrafish embryos or larvae based on transcriptome - Liu, Chunyu; Guo, Yantong; Zhang, Xue; Chen, Hongsong; Han, Maomao; Wang, Han; Niu, Jieyao; He, Jinfei; Yang, Jingfeng; Dong, Wu; Xue, Jiangdong (Frontiers in Veterinary Science, 2025)
BackgroundDeltamethrin (DM) is a broad-spectrum insecticide that is widely used to control agricultural pests. Recently, DM has posed a potential threat to the health of infants and young children, and this is because of the environmental and food pollution that is caused by the extensive use of DM.MethodsIn this study, zebrafish (Danio rerio) embryos were used as experimental animals to quantify the behavioral changes of larvae induced by DM and explore the relationship between DM and acetylcholinesterase activity.ResultsThe results showed that DM caused an increase in coiling movement, heart rate, and apoptosis in the brain in early zebrafish embryos or larvae. It also caused a decrease in the expression of acetylcholinesterase-associated genes and the activity of acetylcholinesterase, which also led to an increase in the acetylcholinesterase content. The transcriptome data also showed that low concentration DM induced acetylcholine-related gene signaling pathways. The above results suggest that low doses of DM may induce neurodegeneration because DM exposure inhibits acetylcholinesterase, leading to brain cell apoptosis and behavioral changes in the zebrafish embryos or larvae. Micro-injection of zebrafish embryos at the 2–4 cell stage knocked down or overexpressed the acetylcholinesterase gene showed that the behavior and enzyme activity of zebrafish had some effects.ConclusionThis study explored the relationship between acetylcholinesterase and the change in zebrafish behavior caused by DM exposure to provide a basis for the treatment of DM poisoning in the aquaculture.